Positivity Status and Molecular Characterization of Porcine Parvoviruses 1 Through 8 (PPV1-PPV8) from Slaughtered Pigs in China - Dashi Zhao; Hong Lin; Zitao Huang; Yajie Zhou; Wenhao Qi; Meng Cui; Ming Qiu; Jianzhong Zhu; Nanhua Chen (Animals)
Porcine parvoviruses one through eight (PPV1-PPV8) are prevalent in Chinese swine herds. However, the infection status of all these PPVs in slaughtered pigs is still unclarified. In this study, we detected PPV1-PPV8 in 353 tissue samples collected from slaughtered pigs from six regions of China in 2023. At least one species of PPV was detected in 79.32% of the samples (280 out of 353). Six PPV species were detected, except for PPV4 and PPV8, in slaughtered pigs, within which PPV3 (49.86%), PPV2 (42.49%), and PPV7 (42.21%) were predominant, followed by PPV1 (13.31%), PPV6 (13.31%), and PPV5 (8.22%). Noticeably, co-infection was frequently detected, with 67.50% of PPV-positive samples (189 out of 280) co-infecting with two to six PPVs. In addition, one representative genome for each detected PPV was determined. Multiple sequence alignment determined a large number of substitutions in capsid proteins of PPVs. Genome-based phylogenetic analysis confirmed the PCR detection results. Recombination detection identified two potential recombinants (PPV2 GDCZ2023-2088 strain and PPV3 HLJSYS2023-1654 strain) in slaughtered pigs. Overall, this study provides new insights into the prevalence and evolution of PPVs, particularly in slaughtered pigs in China.